Targeting the IL-17 Pathway in Inflammatory Disorders - Chu, Cong-Qiu (Springer International Publishing : Imprint: Adis, 2017)
This book provides an overview of the discovery and structure of IL-17, including its pathogenesis and role in chronic inflammation and autoimmunity. To capture the latest developments and product approvals the book also discusses the therapeutic advances and looks at emerging therapies targeting the IL-17 pathway. IL-17 is a pro-inflammatory cytokine that has a key role in inflammation, autoimmunity, and host defense in a number of inflammatory disorders such as rheumatoid arthritis, psoriatic arthritis and psoriasis, ankylosing spondylitis, multiple sclerosis, and inflammatory bowel disease. The discovery of the IL-17-Th17 pathway has seen exciting development in the field of immunology and inflammation research, which has led to a number of recent regulatory approvals.
Keywords: Medicine.; Dermatology.; Public health.; Rheumatology.; Primary care (Medicine).; Pharmacotherapy.; elektronické knihy; electronic books